Stories from My Childhood - Volume 4 - Atamanov, Lev Konstantinovic; Stepancev, Boris; Ivanov-Vano, Ivan Petrovic; Irving, Amy; Curry, Tim; MacLaine, Shirley (image Entertainment, 1999)
Russia's Soyuzmultfilm Studios, one of the most remarkable animation factories of the 20th century, is celebrated in this fourth volume from the PBS series, co-executive produced by Mikhail Baryshnikov. As with previous volumes, this one collects several of Soyuzmultfilm's most dazzling adaptations of European folklore, including a classic 1952 version of "Beauty and the Beast" that is far closer to the original story than Disney's. (Contemporary voicing is provided by Robert Loggia, Tim Curry, and Amy Irving.) A wonderfully fun and painterly version of "The Nutcracker," including Tchaikovsky's music, is narrated by Shirley MacLaine. The collection also includes a pair of adaptations of Pushkin stories, each gorgeous to see and voiced by the likes of Jessica Lange, Timothy Dalton, Gregory Hines, and Cathy Moriarty. Animation buffs will truly enjoy the complexity and lushness of the Soyuzmultfilm style, while kids will appreciate the terrific storytelling and exciting visuals. The DVD has alternate French and Spanish soundtracks with different vocal casts. (Tom Keogh) [www.amazon.com]
Keywords: DVD-Video